STUDENTS PERCEPTION ON THE ONLINE LEARNING: A CASE STUDY OF EFL LEARNERS - Widya Oktarini (Universitas Islam Nahdlatul Ulama Jepara, 2021)
ABSTRACTThis case study aims at describing students perception especially EFL learners on the online learning during the pandemic covid 19. The data was taken from English Department students who are in the second semester which are taught by the researcher in her class. The data collection was done by using online interview by using zoom meeting in which the students enter the meeting one by one to have the interview. Based on the analysis, it revealed that according to students perception, online learning is not effective and not liked by the students. They prefer face-to-face or offline class. In details, they stated some reasons, they are: the unstable signal, cannot adjust yet with the online class, the instruction of the assignment is not clear, not effective group assignment because of online interaction, the material of online learning is not so clear. So, they hope the offline class will be done soon. The online learning tools they like the most is zoom meeting because it is almost like the face to face class.Keywords: Students perception; online learning; EFL Learners.